Biomechanical Changes During a 90º Cut in Collegiate Female Soccer Players With Participation in the 11+ - Celeste Dix; Amelia Arundale; Holly Silvers-Granelli; Adam Marmon; Ryan Zarzycki; Lynn Snyder-Mackler (International Journal of Sports Physical Therapy)
# Background